Unsteady thermally radiative and chemically reactive viscoelastic fluid flow past a vertical porous plate with a heat source. Issue 2 (3rd November 2022) - Muduly, Madan Mohan; Swain, Kharabela; Rath, Pravat Kumar; Parida, Tusar; Dash, Gouranga Charan
Abstract: An analytical study is performed to investigate the thermal radiation effect on the unsteady two‐dimensional magnetohydrodynamic flow of a viscoelastic incompressible fluid (Walters B ′ $B^{′} $ fluid model) along an infinite hot vertical sheet embedded in a porous medium. Further, the addition of a heat source in the energy equation as well as a chemical reaction in the concentration equation renders the present analysis realistic in the field of engineering and technology. The governing equations of mass, momentum, energy, and concentration are solved with successive perturbation techniques. The effects of pertinent parameters on fluid velocity, temperature, concentration, and bounding surface coefficients are shown graphically and in tabular form. The salient feature of the present study is to impose control on magnetic field strength vis‐à‐vis electromagnetic force by regulating voltage in the electric circuit. The important findings are: the elasticity property of the fluid is more sensitive to heated bounding surface consequently free convection current in enhancing the velocity near the plate than the inherent property viscosity. This outcome contributes to the design requirement to control the flow near the heated surface, higher values of frequency parameters contribute to the attainment of a free stream state in temperature distribution. Besides the aforesaid outcome, the present model is conducive to thinning of boundary layer as the elasticity, magnetic as well as free convection parameters enhance the force coefficients at the bounding surface.